Antihypertensive effect of Valyl-Tyrosine, a short chain peptide derived from sardine muscle hydrolyzate, on mild hypertensive subjects - Kawasaki, T; Seki, E; Osajima, K; Yoshida, M; Asada, K; Matsui, T; Osajima, Y (Journal of human hypertension, 2000)
The present study was conducted to determine whether Valyl-Tyrosine (VY) has an antihypertensive effect on high-normal blood pressure and mild essential hypertension, as well as spontaneous hypertensive rats (SHR). A randomised double-blind placebo-controlled study was carried out on 29 volunteers. A 100-ml drink containing 3 mg of VY and a 100-ml placebo drink were prepared. The subjects were grouped as VY(16M/1F, 45.5 +/- 3.2 years, 146.4 +/- 2.3/90.5 +/- 1.8 mm Hg) and the placebo (P) (11 M/1F, 48.8 +/- 3.0 years, 145.5 +/- 2.4/92.3 +/- 1.8 mm Hg). At 3 weeks of the control (C) period, a VY- or P-drink was administered twice a day for 4 weeks in the experimental (E) period and during the 4-week recovery period, neither drink was given to either group. Blood pressure (BP) was measured every week in the morning in the sitting position. Blood specimens were taken on the last day of the C and E periods. In the VY-group, reduction in systolic (S) and diastolic (D) BP was 9.7 and 5.3 mm Hg (P < 0. 001) at 1 week, and 9.3 and 5.2 mm Hg (P < 0.001) at 4 weeks, following the start of the E period, respectively. Neither SBP nor DBP changed in the P-group. BP in the VY-group increased gradually by the end of the recovery period. Plasma angiotensin (Ang) I and VY concentrations significantly increased while Ang II and aldosterone significantly decreased after VY administration in the VY-group. VY appeared to have a significant antihypertensive effect on mild hypertensive subjects via Ang I-converting enzyme inhibition, as well as SHR, but no adverse effects could be detected at all.